2017
DOI: 10.15537/smj.2017.6.19492
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obstructive sleep apnea in children with sickle cell disease at a tertiary hospital in Saudi Arabia

Abstract: Objectives:To assess the prevalence of obstructive sleep apnea in Saudi children with sickle cell disease at a tertiary hospital in Kingdom of Saudi Arabia (KSA) using nocturnal polysomnography.Methods:A prospective cross-section study was conducted between 2012 and 2016 in 65 children aged between 2-14 years at Prince Sultan Military Medical City, Riyadh, KSA with sickle cell disease. Patients answered a pediatric sleep questionnaire with the help of an accompanying caregiver and underwent polysomnography in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…A total of 7 studies reported the prevalence of sleep-disordered breathing in children and adults with SCD (total n 5 489), which ranged from 42% in children to 46% in adults. [72][73][74][75][76][77][78] Using a higher apnea-hypopnea index cutoff in children with SCD resulted in a lower prevalence. In 2 studies that reported cardiovascular outcomes (total n 5 115), sleep-disordered breathing was associated with a higher mean systolic blood pressure and evidence for impaired left-ventricular diastolic dysfunction, and lower nocturnal oxygen saturation was associated with a shorter time to first cerebrovascular event.…”
Section: Recommendationmentioning
confidence: 99%
“…A total of 7 studies reported the prevalence of sleep-disordered breathing in children and adults with SCD (total n 5 489), which ranged from 42% in children to 46% in adults. [72][73][74][75][76][77][78] Using a higher apnea-hypopnea index cutoff in children with SCD resulted in a lower prevalence. In 2 studies that reported cardiovascular outcomes (total n 5 115), sleep-disordered breathing was associated with a higher mean systolic blood pressure and evidence for impaired left-ventricular diastolic dysfunction, and lower nocturnal oxygen saturation was associated with a shorter time to first cerebrovascular event.…”
Section: Recommendationmentioning
confidence: 99%
“…Mbong et al [21] reported a prevalence rate of NE of 100% in children with SCA and OSA compared to 46.2% in those without OSA (P 0.004). In a recent study from Saudi Arabia NE was reported in 62% of children with SCA and Obstructive apneahypoapnea index (OAHI) ≥ 1 compared to an overall prevalence rate of 46% [23]. Lehman and colleagues demonstrated in their study that habitual snoring and SDB with and without habitual snoring are associated with enuresis in children with SCA.…”
Section: Ne and Upper Airway Obstruction Are They Related?mentioning
confidence: 98%
“…Obstructive sleep apnea (OSA) is the commonest of these disorders [57]. Few studies have described sleep-disordered breathing and OSA in children and adolescent with SCA using polysomnography(PSG) [23,[58][59][60][61][62]. OSA was reported in 10-80% of children with Sickle cell disease [58][59][60][61][62]23].…”
Section: Ne and Sleep-related Disorders In Scamentioning
confidence: 99%
See 2 more Smart Citations